Post-exceptionalism and corporate interests in US agricultural policy. Issue 11 (29th November 2017) - Sheingate, Adam; Scatterday, Allysan; Martin, Bob; Nachman, Keeve
ABSTRACT: This paper examines post-exceptionalism in US food and agriculture policy. Using data on lobbying activity and campaign contributions, we find that corporations and organizations representing the banking industry, manufacturers of agricultural inputs, food processors, and the retail food sector allocate significant financial resources trying to influence food and agriculture policy. Although traditional peak associations of farmers and organizations representing the growers of specific commodities remain an important constituency in policy debates, agriculture is no longer a compartmentalized policy domain dominated by producer interests. Instead, food and agriculture resemble other domains of US policy in which corporations and trade associations leverage advantages in money and personnel to protect their bottom line.